Manajemen Penetasan Telur Tetas Ayam Sentul (Studi Kasus di UPTD. Balai Pengembangan Perbibitan Ternak Unggas (BPPTU) Jatiwangi): Hatchery Management of Sentul Chicken Eggs (Case study in UPTD. Poultry Breeding Development Center Jatiwangi) - Suciati, Bella Permata; Herlina, Linda; Kuswaryan, Sondi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
The success indicators for the hatchery program in the management of sentul chicken breeding at the Regional Technical Implementation Unit (UPTD) of the Poultry Breeding Development Center (BPPTU) in Jatiwangi are fertility, hatchability, and salable chicks. UPTD BPPTU Jatiwangi is an institution responsible for the development and improvement of local poultry breeds under the supervision of the Department of Food Security and Animal Husbandry (DKPP) of West Java Province. This research aims to determine the fertility, hatchability, and production of salable chicks from Sentul chickens at BPPTU Jatiwangi. The analysis method used is observation, and the data obtained are analyzed using descriptive statistics. The research was conducted as a case study, using both primary and secondary data. The incubated eggs used had a weight of 41-55 grams and were obtained from UPTD BPPTU Jatiwangi with a male-to-female ratio of 1:5. The observed parameters were fertility, hatchability, and salable chicks. The research results showed an average fertility of 81.62±1.34% with a coefficient of variation of 1.64%, hatchability of 74.64±4.94% with a coefficient of variation of 6.61%, and salable chicks of 96.4±1.65% with a coefficient of variation of 1.71%.